Spontaneous -ignition data of hydrocarbons and aviation fluids - Goodger, E. M. (College of Aeronautics, 1957)
The standard A.S.T.M. method has been used to determine comparative spontaneous-ignition characteristics of 29 hydrocarbons and aviation fluids. Reasonable correlation is found with results from more precise methods. Ignition temperature levels are similar in the case of paraffins, olefins, and naphthenes, but are slightly higher with alcohols, and much higher with aromatics. Ignition temperature of petroleum-based aviation fluids show a general reduction with increase in specific gravity. This note includes work reported in a thesis submitted by F/O. P. Susilvorn, R.T.A.F., in June, 1957 (ref.7), as part of the requirements for the award of the Diploma of the College of Aeronautics, the research being under the supervision of the author.